Assessment of herbaceous vegetation species composition growing around Kleinkopje opencast coal mine, Mpumalanga Province, South Africa - Mangwane, M.; Madakadze, I.C.; Nherera-Chokuda, F.V.; Dube, Sikhalazo; Mndela, M.; Tjelele, J.; Pule, H.T. (2025)
Coal mining involves the removal of natural vegetation, heavy excavation; combustion and ignition accompanied by a release of coal dust to the atmosphere that drastically reduce the ecosystem services. A study was conducted to assess of veld grasses around a coal mine in Emalahleni in Mpumalanga. Six 100 m line transects were established on rehabilitated site and natural veld in Kleinkopje coal mine. Plant identification, leaf and tiller counting, and biomass harvesting were conducted on each of five 1 m2 sampling quadrats placed at intervals of 20 m along the transect. Nineteen (19) grass species, some (07) forbs and (03) sedges were recorded. Therefore, Eragrostis curvula (31.5%) was the most frequent on the natural veld, followed by Cynodon dactylon (28.36%) and Panicum maximum (22.25%) on the rehabilitated. On the natural veld, Aristida congesta had higher tiller production (17 tillers per plant) while E. curvula averaged 11 tillers per plant on the rehabilitated site. On the rehabilitated site, U. mosambicensis produced averaged 94 leaves per plant than all other species on both sites. Basal cover, species diversity and richness did not differ (p > 0.05) between rehabilitated site and natural veld. Rehabilitated site had a generally higher biomass production of 4.35 kg DM ha− 1 than natural veld with 3.24 kg DM ha− 1. E. curvula and C. dactylon had higher contribution to the total biomass production on both sites. However, their biomass production was insignificantly different (p > 0.05) from that of Urochloa mozambicensis and P. maximum on rehabilitated site and Heteropogon contortus on natural site. Our results indicated that E. curvula and C. dactylon are highly persistent and productive hence they are ideal for mine rehabilitation.